2012
DOI: 10.1002/ibd.21307
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory bowel disease-associated thromboembolism: A systematic review of outcomes with anticoagulation versus catheter-directed thrombolysis

Abstract: CDT and AC both appear to be well tolerated by IBD patients with TE. CDT may be used preferentially in patients with life-threatening TE, while AC may be preferable in patients with less clinically significant TE or patients at higher risk for bleeding. Further prospective studies are warranted to confirm these results and more definitively identify the best therapeutic approach for patients with IBD-associated TE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…have been suggested as additional predisposing factors that increase the risks of venous thromboembolism (58,(58)(59)(60). Studies have shown that these interventions can precipitate a transient hyper-coagulative phase in the vascular system which might further increase the risks of venous thromboembolism in inflammatory bowel disease patients (61,62).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…have been suggested as additional predisposing factors that increase the risks of venous thromboembolism (58,(58)(59)(60). Studies have shown that these interventions can precipitate a transient hyper-coagulative phase in the vascular system which might further increase the risks of venous thromboembolism in inflammatory bowel disease patients (61,62).…”
Section: Discussionmentioning
confidence: 99%
“…These inflammatory changes lead to the development of Virchow's triad (vascular injury, hemostasis, and hypercoagulation), ultimately resulting in increased incidence of venous thromboembolism ( 56 , 57 ). In the existing literature, even the therapeutic interventions (i.e., steroid therapy, abdominal surgery, central venous catheter) generally administered to manage inflammatory bowel disease have been suggested as additional predisposing factors that increase the risks of venous thromboembolism ( 58 , 58 60 ). Studies have shown that these interventions can precipitate a transient hyper-coagulative phase in the vascular system which might further increase the risks of venous thromboembolism in inflammatory bowel disease patients ( 61 , 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, early clinical trials using heparin as treatment for severe steroid‐refractory UC suggested anticoagulants are safe with respect to complications of bleeding . Furthermore, catheter‐directed thrombolysis has been used for IBD‐associated thromboembolism and appears to be well tolerated in terms of haemorrhagic complications . Current ECCO practice guidelines for the management of IBD advocate the use of antithrombotic prophylaxis in all hospitalised UC and CD patients .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the primary gastrointestinal manifestations of IBD, a wide-range of extra-intestinal manifestations (EIMs) have also been reported[ 3 , 4 ]. One of the well-recognized EIMs of IBD is the increased risk of thromboembolic phenomena[ 5 - 7 ]. Several recent studies have demonstrated a two to four-fold increased risk of atherosclerotic cardiovascular disease (ASCVD) in patients with IBD as compared to the general population[ 8 ].…”
Section: Introductionmentioning
confidence: 99%